ANALISIS KARAKTERISTIK DAN KEPUASAN PELANGGAN UNTUK MENINGKATKAN TINGKAT HUNIAN PADA WISMA BALAI PRODUKSI DAN INFORMASI AUDIO VISUAL SURABAYA - Ivo Fauziah; Hitapriya Suprayitno; I Putu Artama Wiguna (Institut Teknologi Sepuluh Nopember, 2018)
The paper disccuses an analysis study on customer characteristic and satisfaction. The analysis is performed by gap analysis and Importance Performance Analysis.Each indicator mapped on IPA diagram to indicate the priority attributes needs to be fixed. The results showed that most customers (61%) have the purpose of training. Attributes that are identified in A quadrant, i.e. the main priority of improvement are the wi-fi facilities (to support training activities), emergency safety facilities (to ensure customer with long periods staying feel secure), facilities and room furniture (to support customer to store their goods), and also price discounts to attract more customers. Marketing approach trough advertising and promotion will support the dissemination of information that can increase the number of residential homestead.